Enhanced thermal conductivity of poly(L-lactide) composites with synergistic effect of aluminum nitride and modified multi-walled carbon nanotubes. Issue 10 (2nd October 2016) - Du, Fei-Peng; Li, Jing-Jing; Fu, Ping; Wu, Yan-Guang; Liao, Gui-Ying; Zhang, Yun-Fei; Luo, Shuai
ABSTRACT: Poly (ethylene glycol)-grafted multi-walled carbon nanotubes (PEG-MWNTs) were prepared and added into poly(L-lactide) (PLLA)/aluminum nitride (AlN) composites to obtain PLLA/AlN/PEG-MWNTs nanocomposites. Microstructure and thermal conductivity of the composites were investigated on the basis of the influence of PEG-MWNTs incorporated. The results showed that PEG-MWNTs were well-dispersed in the PLLA matrix and had strong interfacial adhesion with the matrix. The addition of PEG-MWNTs improved the thermal conductivity of PLLA/AlN composites. When 3 wt.% of PEG-MWNTs and 50 wt.% of AlN were both added into the PLLA matrix, the thermal conductivity reached 0.7734 W/mK with enhancement almost by 400% as compared to a neat PLLA. However, the thermal conductivity is 0.3401 W/mK for the PLLA composite with 3 wt.% of PEG-MWNTs and 0.4286 W/mK for the one with 50 wt.% of AlN. The synergistic effect of aggregated AlN particles and well-dispersed MWNTs could form efficient thermal conductive paths for improving the thermal conductivity of PLLA composites greatly.